The Role of the Bandwagon Effect, Financial Technology, and Financial Literacy in the Investment Interests of Generation Z in Bali - Ratihningih, Ni Kadek Sri; Astiti, Ni Putu Yeni; Mentari, Ni Made Indah (Universitas Negeri Gorontalo, 2024)
Purpose: This study aims to determine and explain the influence of the bandwagon effect, financial technology, and financial literacy on the increased interest in investment among Generation Z in Bali.Design/Methodology/Approach: The population in this study consists of all Generation Z individuals in Bali, while the sample in this research is determined using the purposive sampling method. The determination of the sample size is carried out using the unknown population formula because the exact population size is not known, resulting in a total sample of 100 respondents. The type of data used is primary data obtained from the responses to statements in a questionnaire that has been distributed to Generation Z respondents. The data analysis methods used include validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, t-test, and F-test.Findings: The results indicate that the bandwagon effect, financial technology, and financial literacy have a positive and significant influence on the increased investment interest of Generation Z in Bali.